'The Last Arrival Point': The refugee experience of resettlement in Ireland. (May 2022) - Watters, Cynthia; Mowlds, William; O'Connor, Anne; M Sarma, Kiran
Abstract: Background: Programme Refugees are refugees who are invited into a country by its government in response to a request for protection from the United Nations High Commissioner for Refugees. The increase in arrivals of Programme Refugees to Ireland has received a lot of attention to date. With financial support from the European Union, Ireland intends to grant entry to a further 2900 Programme Refugees via this unique pathway known as the Irish Refugee and Protection Programme (IRPP) between 2020 and 2023. This novel research explores the experiences of Programme Refugees resettling in Ireland within a psychological framework. Method: This research adopted an exploratory approach using a qualitative framework. Semi-structured interviews were conducted with nine Programme Refugees living in the community (5 male, 4 female) with an average age of 37 years. The average length of time in Ireland was 33 months, of which an average of 25 months was spent resettled in permanent housing. Results: Codebook thematic analysis underpinned by a critical realist epistemology was used to analyse the data. Two key themes were identified; " The home change our life" and "I can start my new life" . Conclusion: This research obtains the refugee's perspective and personal insights of availing of the IRPP and resettling in Ireland. Although the purposive sampling reduces the generalisability of findings to Programme Refugees resettled in the West of Ireland, this research offers an awareness and understanding of a Programme Refugee's journey towards resettlement and the impact it can have on their mental health and psychological well-being. This research has implications for national and European resettlement policies, and it is hoped that it can be used to guide the development of future resettlement programmes internationally.